Assessing the compliance of employers in contract agreement towards foreign employees in maintenance works / Morsidi Ayob - Ayob, Morsidi (Faculty of Architecture , Planning and Surveying, 2015)
Malaysia nowadays has approximately over 1.9 million foreign workers spread across sectors such as in a manufacturing industry 39%, construction 19 per cent%, plantation 14%, housemaids 12% , services with 10%, and another 6% is in agriculture. Moreover, the contributing countries by rank are: Indonesia 50.9%, Bangladesh 17.4%, Nepal 9.7%, Myanmar 7.8%, India 6.3%, and another 7.9% is from Vietnam. For the employers who hire a migrant worker, they must be fully protect his worker and his own by a Contract of Employment. An employment contracts is important to protect the rights of employee and employer.Employment contract is a contract which stipulates terms and conditions on duration, wages, work shift, days off, sick leave, medical fees, payment of levy,visa, medical, wages, welfare, safety and other related to worker rights. Contract agreement proves that employee accept the terms and conditions offered by the employer. Law that apply to migrant worker in Malaysia such as under Employment Act 1955, Trade union Act 1959, Industrial Relation Act 1967,Occupational Safety and Health act 1994, Wages Council 1947, Children & Young Person Act 1952, Work Compensation Act and some more. The content of employment contracts usually will outline how long the contract is valid for the employee to stay with a company. If one of the both party breaches the contract,the fault party will be imposed for the penalty, both of the employee and the employer can end the employment agreement at any time as long the cancellation of contract has been agree by the both party. The contract starts immediately when the offer of employment is accepted. The objective of this research is to allocate the current employment contract application in achieving an excellent agreement between the employers and employees, to examine the compliance of contract agreement by employers toward employees and to evaluate the employees’ satisfaction toward compliance of current practice of contract agreement by the employers. Data of this research was collected through a semi-structure interview, distribution of questionnaire form and observation. The main finding revealed that the four (4) outsources contractors' with similarity in employing a foreign employees in maintenance works.